2011
DOI: 10.1016/j.jamda.2010.08.015
|View full text |Cite
|
Sign up to set email alerts
|

Advance Directive and End-of-Life Care Preferences Among Chinese Nursing Home Residents in Hong Kong

Abstract: Most of our cognitively normal Chinese nursing home older adults prefer having an advance directive, and one-third of them would prefer to die in nursing homes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
82
3
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(95 citation statements)
references
References 38 publications
9
82
3
1
Order By: Relevance
“…They were willing to discuss ACP and their AD preferences. Contrary to the taboo belief and consistent with the studies of nursing home residents, 3,4 about 80% of elders preferred to have a say in decision making. In contrast, only 15.1% of family members felt comfortable to make a decision themselves without involving the elder.…”
supporting
confidence: 54%
See 1 more Smart Citation
“…They were willing to discuss ACP and their AD preferences. Contrary to the taboo belief and consistent with the studies of nursing home residents, 3,4 about 80% of elders preferred to have a say in decision making. In contrast, only 15.1% of family members felt comfortable to make a decision themselves without involving the elder.…”
supporting
confidence: 54%
“…However, studies of Hong Kong nursing home residents revealed that elders preferred to voice their wishes. 3,4 In general, nursing home residents are more disable and frail, and at a late stage of their life.…”
mentioning
confidence: 99%
“…The proportion that rejected active treatment near the end of life was much lower than those reported in a Hong Kong Chinese nursing home study, which found that more than half of the residents did not want CPR and artificial nutrition to be started. 7 However, unlike our study, the Hong Kong study did not explore the residents' life-sustaining treatment experiences, 7 which may have contributed to these different results. In another study, 92% of Canadian caregivers who had provided end-of-life care to family indicated that they would in the future reject futile life-sustaining treatment to extend life, 29 suggesting that people with previous life-sustaining treatment experiences may be more likely to reject this level of intervention in the future, but this notion needs to be further explored.…”
Section: End-of-life Care Preferences Among Nursing Home Residentsmentioning
confidence: 66%
“…7 Another Hong Kong study identified that many nursing home residents were uncertain or uncomfortable when asked about stating their preferences for life-sustaining treatment, with many leaving this question unanswered. 6 In traditional Chinese culture, death is a very sensitive issue, and a topic to be avoided, with those who do mention death considered sacrilegious.…”
mentioning
confidence: 99%
“…Another option is for the patient to sign an AD, a formal tool that respects the autonomy of patients and in which any decision must be adhered to by the health care team. 28 In Hong Kong, life-sustaining treatment, including tube feeding, can be withheld if there is a valid AD when the patient is in an irreversible coma, persistent vegetative state, terminal illnesses, or other end-stage irreversible life-limiting condition. 29 Nonetheless until recently ACP and AD have been seldomly discussed in Hong Kong.…”
Section: Lack Of An Advance Directive and Advance Care Planningmentioning
confidence: 99%